Pricing to Market and the Real Exchange Rate - Faruqee, Hamid (IMF Working Papers; Working Paper ;, 1995)
This paper investigates the consequences of pricing to market for exchange rate pass-through and real exchange rate dynamics across different patterns of trade under market segmentation. Under two-way, intraindustry trade--where home prices display greater linkage with those of foreign competitors--domestic and export prices exhibit lower pass-through and greater destination-specific adjustment compared to intersectoral trade. With both trade patterns, pricing-to-market behavior intensifies the degree of persistence in the real exchange rate under nominal rigidities, and allows monetary shocks to have permanent effects on relative prices when goods markets remain segmented.